National Prevalence and Risk Factors for Food Allergy and Relationship to Asthma: Results from the National Health and Nutrition Examination Survey 2005-2006 - Liu, Andrew H. (2010)
BACKGROUND: The national prevalence and patterns of food allergy (FA) in the United States (US) are not well understood. OBJECTIVE: We developed nationally representative estimates of the prevalence of and demographic risk factors for FA, and investigated associations of FA with asthma, hay fever, and eczema. METHODS: 8,203 participants in the National Health and Nutrition Examination Survey (NHANES) 2005–2006 had food-specific serum IgE measured to peanut, cow's milk, egg white, and shrimp. Food-specific IgE and age-based criteria were used to define Likely FA (LFA), Possible FA (PFA), and Unlikely FA (UFA), and to develop estimates of clinical FA. Self-reported data were used to evaluate demographic risk factors and associations with asthma and related conditions. RESULTS: In the US, the estimated prevalence of clinical FA was 2.5% (peanut 1.3%, milk 0.4%, egg 0.2%, shrimp 1.0%, not mutually exclusive). Risk of PFA/LFA was increased in non-Hispanic blacks (odds ratio (OR) 3.06; 95% confidence interval (CI) 2.14-4.36), males (1.87; 1.32-2.66), and children (2.04; 1.42-2.93). Study participants with doctor-diagnosed asthma (vs. no asthma) exhibited increased risk of all measures of food sensitization. Moreover, in those with LFA, the adjusted OR for current asthma (3.8; 1.5-10.7) and an emergency room (ER) visit for asthma in the past year (6.9; 2.4-19.7) were both notably increased. CONCLUSION: Population-based serologic data on 4 foods indicate an estimated 2.5% of the US population has FA, and increased risk was found for blacks, males, and children. Additionally, FA could be an under-recognized risk factor for problematic asthma.